Voltammetric reduction of Ellagic acid nanocomposite Using Carbon nanotube -Modified Glassy Carbon Electrode - Mohammed Zidan, Samer Al-Ali, Mohamed Ahwidi , Asmaa Ali (Journal of Pure & Applied Sciences, 2018)
A new ellagic acid nanocomposite (EAN) based on zinc-layered hydroxide (ZLH) intercalated with an ellagic acid (EA ) was synthesized through direct reaction of ellagic acid at 0.01 and 0 .025 Mol/L concentrations with commercially available zinc oxide. The basal spacing of the pure phase nanocomposite was 10.4 Å.”“The release of the ellagic acid from the nanocomposite was found to be sustained, and the maximum amount of ellagic acid released is almost 98% of the total at pH 4.0 phosphate buffer saline solution (PBS). A very sensitive electrochemical sensor has been developed by modification of glassy carbon electrode (GCE) with carbon nanotubes (MWCNT ). The electrochemical behaviour of ellagic acid was studied at MWCNT/GCE using cyclic voltammetry . A well defined reduction peak was observed in 0.1 M KCl electrolyte solution by solid phase voltammetry. Under the CV techniques, it appears that the catalytic effect of the modification of MWCNT/GCE show higher current response as compared to bare GCE. Peak potential was observed to shift slightly to less positive value by about 220 mV and current was significantly enhanced by about 2.3 folds.